How singleton breech babies at term are born in France: a survey of data from the AUDIPOG network. (May 2015) - Lansac, J.; Crenn-Hebert, C.; Rivière, O.; Vendittelli, F.
Abstract: Based on data from the AUDIPOG sentinel network between 1994 and 2010, we can say that the rate of singleton breech presentation at term is 3% and remains unchanged despite an external cephalic version rate of 35%. The total cesarean section rate is currently 75%. This rate increased by nearly 20% after the Hannah publication in 2000, regardless of the type of breech and type of maternity unit. The rate of planned cesarean sections increased in particular, going from 40% to 60%, and even reaching 67% for footling breech presentations. The rate is higher in type I maternity units than in type II or III. This cesarean section rate has been stable since 2005 and has even decreased for the Frank breech. The average rate of external cephalic version remains stable at around 23%. The episiotomy rate is 28%. The rate of babies transferred to neonatology units is higher for breech babies at term than for babies presenting cephalically (3.9% compared to 2.9%), but the newborns most often transferred are those born by cesarean section (4.1% compared to 3.4%).